Treatment of high-strength wastewater from the sugar-sweetened beverage industry by an alcoholic fermentation process - Comelli, Raul Nicolas (2015)
Certain wastewaters from the nonalcoholic sugar-sweetened beverage industry, particularly those discarded because of deficient bottling processes or those returned from the market because of quality constraints, exhibit chemical oxygen demand (COD) levels as high as 135000 mg of O2/L because of their sugar content: 60−119 g/L, depending on the beverage. Thus, treating such wastewaters before discharging them into the environment involves high investment and operating costs. Therefore, any treatment process capable of transforming the sugars into other compounds that are easy to separate from the treated wastewater, such as ethanol or CO2, should be regarded as an interesting alternative. In this work, a process that comprises an alcoholic fermentation of sugar-sweetened beverage industry wastewaters followed by ethanol and biomass separation and subsequent aerobic propagation of yeast was developed, and its technical feasibility was studied. The proposed process was found to allow 98% of the COD to be depleted.